2019
DOI: 10.20527/flux.v16i1.5876
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Reduced Graphene Oxide from Fiber of Borassus Flabelifer by Activation Method

Abstract: Reduced Graphene Oxide (RGO) has been successfully synthesized by calcination process at 4000C for 4 hours followed by activation with NaOH 1 M. Carbonization is the last process with variations in heating at 6500C, 7500C, 8500C, and 9500C for 1 hour (heating rate 100C / minute). DSC-TGA data shows that there is advanced decomposition at high temperatures, this is confirmed by SEM data which shows the amount of porosity which is getting higher with a size that decreases with temperature. XRD data shows phase d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The heating causes decomposition of the impurity compound which makes it leave the material and leaves a hole in the form of a pore. Based on the DSC-TGA graph by Fandi, et al [13] on fibers Borassus Flabelifer L, decomposition occurs especially in liginine from 200°C to 600°C. In this study, based on SEM results, it was shown that the pores formed were < 10 μm in size.…”
Section: Morphology Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The heating causes decomposition of the impurity compound which makes it leave the material and leaves a hole in the form of a pore. Based on the DSC-TGA graph by Fandi, et al [13] on fibers Borassus Flabelifer L, decomposition occurs especially in liginine from 200°C to 600°C. In this study, based on SEM results, it was shown that the pores formed were < 10 μm in size.…”
Section: Morphology Datamentioning
confidence: 99%
“…In this study, a material in the form of fiber of Borassus flabelifer L was used which had not previously been used as a dye adsorbent for textile waste. In a previous study, the fiber of Borassus flabelifer L was treated to form Reduced Graphene Oxide (RGO) phase [13] in order to enhance the adsorption efficiency which was applied as a supercapacitor electrode [14]. In this study, Fiber of Borassus Flabelifer L was treated with different treatments to form RGO phase as well, so that it is expected to be able to absorb textile color waste better.…”
Section: Introductionmentioning
confidence: 99%